2017
DOI: 10.1136/bmjinnov-2017-000202
|View full text |Cite|
|
Sign up to set email alerts
|

Paediatric neurorehabilitation: finding and filling the gaps through the use of the Institute for Manufacturing strategic roadmapping method

Abstract: IntroductionAcquired brain injury (ABI) is a major cause of morbidity and mortality in childhood. Specialist rehabilitation services are often situated far from families and local services may be non-standardised and fragmented. A strategic level of understanding is needed to improve patient care and outcomes. Roadmapping techniques are commonly used in industry settings to discover and present a systematic understanding of structures; however, they are rarely used in the healthcare setting. With continuing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Prioritization of these goals would be expected, as they contain activities that are tangible and meaningful to the child. Indeed, given that successful participation in activities at home, school, and the community is the overall aim of rehabilitation programmes (Hamilton et al, ), consideration of these types of goals would have been encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Prioritization of these goals would be expected, as they contain activities that are tangible and meaningful to the child. Indeed, given that successful participation in activities at home, school, and the community is the overall aim of rehabilitation programmes (Hamilton et al, ), consideration of these types of goals would have been encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Acute and post-acute neuro-rehabilitation for CYP with ABI is delivered by 16 regional specialist centres across the UK. National service specifications for paediatric neurorehabilitation aimed for equitable provision across the country, however, there is widespread concern regarding the variability of service provision and a drive towards identifying and commissioning optimum rehabilitation models (2,5,12). Research regarding rehabilitation for adults with brain injury has demonstrated the benefits and cost effectiveness of comprehensive rehabilitation models, this is yet to be fully investigated in paediatric rehabilitation or the impact on the life course of the CYP and family (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important consideration, particularly in an acute hospital setting where making timely assessments and onward referrals are considered to be essential (NHS England, 2014). Such an early indicator may also provide benefit at a ward-based level in order to better orientate and prepare the child and family for what their rehabilitation journey may look like from an early time point; a repeated issue described in the literature (Hamilton et al, 2017). To gain an understanding of the wider validity of the findings related to initial rate of change, further work in other cohorts is required.…”
Section: Rate Of Changementioning
confidence: 99%
“…Acquired brain injuries can lead to a range of both short-and long-term deficits, affecting motor, cognitive and behavioural functions (UKABIF, 2013). Some children admitted to an acute hospital setting will require a period of neurorehabilitation before being able to be discharged (Hamilton et al, 2017). During their acute hospital stay, essential medical care will either precede or run alongside the delivery of acute neurorehabilitation.…”
Section: Introductionmentioning
confidence: 99%